2021
DOI: 10.56126/72.3.7
|View full text |Cite
|
Sign up to set email alerts
|

Management of anesthesia for surgery in prone position for a patient with hereditary neuropathy with liability to pressure palsies. A case report and narrative literature review

Abstract: The reported case describes a patient with hereditary neuropathy with liability to pressure palsies (HNPP) requiring a neurosurgical laminotomy procedure for an arachnoid cyst with medullary compression. HNPP is a rare pathology requiring meticulous anesthetic and surgical management. We give a detailed overview of the planning, simulation, and performance of the anesthesia procedure in order to minimize all potential risk factors for perioperative nerve injury. During the preparation of this case, where the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 23 publications
0
0
0
Order By: Relevance
“…Multidisciplinary discussions can aid in treatment planning when anticipated deviation from the standard of care is necessary. Patient involvement in this process, and implementing the "shared consent" concept, seems prudent [57,79]. Documenting any pre-existing neuropathies also seems prudent practice.…”
Section: Anesthetic Managementmentioning
confidence: 99%
See 1 more Smart Citation
“…Multidisciplinary discussions can aid in treatment planning when anticipated deviation from the standard of care is necessary. Patient involvement in this process, and implementing the "shared consent" concept, seems prudent [57,79]. Documenting any pre-existing neuropathies also seems prudent practice.…”
Section: Anesthetic Managementmentioning
confidence: 99%
“…In prone positioning cases, limbs should be wrapped in quilted cloth and protected with gel pads, paying attention to the nerves most susceptible to damage. For procedures lasting longer than three hours, incorporating ten-to-fifteen-minute breaks every hour to reassess and readjust limb position can be highly beneficial, as described below [79].…”
Section: Pre-induction Periodmentioning
confidence: 99%
“…Therefore, in this case, upper extremity motor and sensory deterioration due to HNPP were also considered. Genetic testing for the detection of a deletion or a point mutation of PMP22 genes, located at chromosome 17p11.2-12, is known as the gold standard for the diagnosis of HNPP 14) . However, genetic testing usually takes more time to confirm the result than CSF analysis.…”
Section: Wwwthenervenetmentioning
confidence: 99%
“…Fortunately, intravenous immunoglobulin (IVIg) is known to be effective in alleviating symptoms and preventing complications in both GBS and HNPP, which are demyelinating peripheral polyneuropathies 1,4,14) . The randomized controlled trial of van der Meché et al 19) in 1992 first showed that the use of IVIg in GBS is as effective as plasma exchange.…”
Section: B B C C D D a Amentioning
confidence: 99%